Pseudoaneurysm of the vertebral artery in the neck - Pierri, Néstor (Cirugía del Uruguay, 1997)
Due to the infrequency of the situation, the author presents a case of post-traumatic pseudoaneurysm of the vertebral artery in the neck of a young five months befare she had suffered a lateral wound in the neck due to stab wound.